2001
DOI: 10.1080/000164801750388027
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Blood Flow Measurement in Patients with Me´nie`re's Disease and Other Inner Ear Disorders

Abstract: Selmani Z, Pyykkö I, Ishizaki H, Marttila TI. Cochlear blood ow measurement in patients with Ménière's disease and other inner ear disorders. Acta Oto Laryngol 2001; Suppl 545: 10 -13.To identify an eventual vascular aetiology in different diseases with sensorineural hearing loss (SNHL), the cochlear blood ow (CoBF) was measured using laser Doppler owmetry (LDF) in 69 patients with Ménière's disease (MD), 38 patients with progressive SNHL and 8 patients with sudden deafness. The mean CoBF amplitude at rest was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 15 publications
(17 reference statements)
0
10
0
1
Order By: Relevance
“…Another study found considerably higher transmission coefficients through the human promontory (49). Nonetheless, Doppler flowmetry has been applied clinically (15,17,25,51). However, the inability of Doppler methods to provide data on flow speeds within specific areas of the cochlea is a major limitation that intravital optical imaging is well suited to address.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study found considerably higher transmission coefficients through the human promontory (49). Nonetheless, Doppler flowmetry has been applied clinically (15,17,25,51). However, the inability of Doppler methods to provide data on flow speeds within specific areas of the cochlea is a major limitation that intravital optical imaging is well suited to address.…”
Section: Discussionmentioning
confidence: 99%
“…These measurements have generally involved laser Doppler techniques (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25), which cannot resolve the blood supply to specific cochlear regions, such as the stria vascularis (8) or basilar membrane (1), that are implicated in forms of sensorineural hearing loss. Ultrasound and magnetic resonance imaging are poorer still in this regard and, although unable to resolve cochlear blood flow directly, have revealed clinical correlations between hearing loss and intracranial circulatory disruptions outside the cochlea (7,(26)(27)(28).…”
mentioning
confidence: 99%
“…They showed a decrease in CBF in patients during administration of the intravenous anesthetic propofol. Other studies have shown changes in CBF in patients with MeniereÕs disease, sudden hearing loss (Selmani et al, 2001), and perilymphatic fistula (Nakashima and Yanagita, 1995). Alteration of the cochlear microcirculation via round window drug application has also been studied (Haapaniemi et al, 2001;Miller et al, 1994).…”
Section: Introductionmentioning
confidence: 98%
“…The vascular etiology of ISHL has been discussed in numerous studies, most of them arguing that the suddenness of the event and the anatomical design of the cochlear vasculature, with the labyrinthine artery being a functional end-artery, make an underlying vascular event rather likely [7] (see Fig. 1).…”
mentioning
confidence: 98%